2019
DOI: 10.1029/2018ja026107
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric GNSS Imagery of Seismic Source: Possibilities, Difficulties, and Challenges

Abstract: Up to now, the possibility to obtain images of seismic source from ionospheric Global Navigation Satellite Systems (GNSS) measurements ( seismo‐ionospheric imagery ) has only been demonstrated for giant earthquakes with moment magnitude Mw ≥ 9.0. In this work, we discuss difficulties and restrictions of this method, and we apply for the first time the seismo‐ionospheric imagery for smaller earthquakes. The latter is done on the example of the Mw7.4 Sanriku‐oki earthquake of 9 March 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…The location of these two TEC enhancements corresponded to the location of two segments of coseismic crustal slip as it was shown by seismologists (e.g., Simons, ; Bletery et al, ; Figure a). More recently, Thomas et al () and Astafyeva and Shults () demonstrated that the GNSS seismo‐ionospheric imagery can work for moderate earthquakes as well. Astafyeva and Shults () also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently.…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
See 2 more Smart Citations
“…The location of these two TEC enhancements corresponded to the location of two segments of coseismic crustal slip as it was shown by seismologists (e.g., Simons, ; Bletery et al, ; Figure a). More recently, Thomas et al () and Astafyeva and Shults () demonstrated that the GNSS seismo‐ionospheric imagery can work for moderate earthquakes as well. Astafyeva and Shults () also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently.…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
“…More recently, Thomas et al () and Astafyeva and Shults () demonstrated that the GNSS seismo‐ionospheric imagery can work for moderate earthquakes as well. Astafyeva and Shults () also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently.…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to determining the locations of seismic sources, GNSS‐based observations of the TEC perturbations above the epicentral zone can contain information on the source dimensions, slip mode, and rupture propagation (Astafyeva et al, , Astafyeva, Rolland, et al, ; Heki et al, ; Rolland et al, ). In particular, high‐rate (1 Hz) GNSS TEC data can provide ionospheric images of the seismic source, in which the position and dimension of initial TEC enhancement correspond to the crustal uplift region (Astafyeva & Shults, ). Given the availability of high‐rate GNSS TEC observations covering the near epicentral zone, regions of uplift can be retrieved from TEC data within 10 min after the main shock, which may be faster and even more accurate than the result obtained from preliminary seismic slip models.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%
“…Observations of the ionospheric disturbances near field of an earthquake of magnitude 7.8 found two N‐shape waves in the TEC disturbance time series (Li et al, ). In addition, another study by Astafyeva and Shults () raised the question of whether a moderate earthquake can generate shock acoustic waves like the most intense earthquakes do. Moderate and small surface disturbance events may well generate weak upper atmospheric signatures that could be comparable to the noise level of some of the existing observational techniques.…”
Section: Most Recent Advances and Future Directionsmentioning
confidence: 99%